Stringy CFT duals with N $$ \mathcal{N} $$ = (2, 2) supersymmetry - Matthias R. Gaberdiel; Jeremy A. Mann (Journal of High Energy Physics)
Abstract It was recently shown that string theory on AdS3× S3× T $$ \mathbbm{T} $$ 4 with minimal NS-NS flux (k = 1) is exactly dual to the symmetric orbifold of T $$ \mathbbm{T} $$ 4. Here we show that a similar statement also holds for the Dn orbifolds of these backgrounds that have N $$ \mathcal{N} $$ = (2, 2) supersymmetry. In this case the CFT dual is the symmetric orbifold of T $$ \mathbbm{T} $$ 4/Dn.